1981
DOI: 10.1111/j.1476-5381.1981.tb10440.x
|View full text |Cite
|
Sign up to set email alerts
|

Opiate‐like Analgesic Activity in General Anaesthetics

Abstract: 1 The interaction of naloxone with various anaesthetics was studied both in vivo and in vitro.2 Naloxone (10mg/kg) did not significantly alter the anaesthetic duration of halothane, diethylether, ketamine, pentobarbitone or Althesin.3 Naloxone (10 mg/kg) reduced the analgesic activity of nitrous oxide, ketamine and morphine in the rat tail-flick test. With the exception of pentobarbitone and Althesin, the other anaesthetic agents also induced analgesia but were not antagonized by naloxone. (IC50 = 40 nM). 6 On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…This was confirmed by another study in which naloxone failed to alter the MAC values for halothane, enflurane and isoflurane (Levine et al, 1986). However, comparable doses of naloxone markedly reduced the antinociceptive effect of ketamine and nitrous oxide but not halothane, diethylether or xylazine (Smith et al, 1978;Lawrence and Livingston, 1981). In another study, naloxone and naltrexone asymmetrically shortened the sleeping times induced by ketamine, halothane, or pentobarbital; high-dose naltrexone was less effective than lower doses in producing this analeptic effect suggesting this action was unrelated to blockade of opioid receptors (Kraynack and Gintautas, 1982).…”
Section: An Opioid Component To General Anesthesia?supporting
confidence: 61%
See 1 more Smart Citation
“…This was confirmed by another study in which naloxone failed to alter the MAC values for halothane, enflurane and isoflurane (Levine et al, 1986). However, comparable doses of naloxone markedly reduced the antinociceptive effect of ketamine and nitrous oxide but not halothane, diethylether or xylazine (Smith et al, 1978;Lawrence and Livingston, 1981). In another study, naloxone and naltrexone asymmetrically shortened the sleeping times induced by ketamine, halothane, or pentobarbital; high-dose naltrexone was less effective than lower doses in producing this analeptic effect suggesting this action was unrelated to blockade of opioid receptors (Kraynack and Gintautas, 1982).…”
Section: An Opioid Component To General Anesthesia?supporting
confidence: 61%
“…Naloxone failed to alter the duration of anesthesia induced by halothane, diethylether, ketamine pentobarbital, Althesin (a mixture of alphaxalone and alphadolone) or hyperbaric nitrous oxide as determined by recovery of righting reflex (Bennett, 1978;Smith et al, 1978;Lawrence and Livingston, 1981). This was confirmed by another study in which naloxone failed to alter the MAC values for halothane, enflurane and isoflurane (Levine et al, 1986).…”
Section: An Opioid Component To General Anesthesia?mentioning
confidence: 53%
“…Xylazine has been shown to possess activity in the rat tail flick analgesic test and to be capable of displacing radiolabelled dihydromorphine in rat brain membrane preparations (Lawrence & Livingston, 1981a). Clonidine has been shown to reverse withdrawal symptoms in opiate addicts (Gold, Redmond & Kleber, 1978) and an overlap in the distribution of x2-adrenoceptors and opiate receptors in the rat brain has been demonstrated autoradiographically (Young & Kuhar, 1979;.…”
Section: Introductionmentioning
confidence: 99%
“…The object of this study was to investigate the interactions between the drugs which react with a2-receptors and those which exert their effects via Guinea-pig ileum bioassay: portions of guinea-pig ileum were suspended in an organ bath in Krebs bicarbonate solution as described by Paton & Vizi (1969 Pert & Snyder (1973) as described by Lawrence & Livingston (1981a) …”
Section: Introductionmentioning
confidence: 99%
“…The relation of the opiate system to ketamine anesthesia and analgesia is uncertain. Some reports showed that these effects were blocked by the opiate antagonist naloxone (STELLA et al, 1981;FINCK and NGAI, 1982), whereas others found no evidence for such an action (LAWRENCE and LIvINGsToN, 1981;WILEY and DOWNS, 1982). The role of the opiate system in the respiratory effect of ketamine has not yet been elucidated.…”
mentioning
confidence: 99%